Basic concepts of behavioral pharmacology - Gonçãlves, Fábio Leyser [UNESP] (Springer Nature, 2021)
This chapter intends to present some concepts, methods, and contributions of Behavioral Pharmacology to the understanding of the phenomenon of substance dependence. The chapter begins with a brief description of the area and history of behavioral pharmacology. Next, it presents basic concepts of pharmacology and neurobiological processes involved in the action of psychotropic substances, seeking to help the reader to develop a basic repertoire that helps him/her to face the challenges of an interdisciplinary area. Among the main concepts approached are absorption, distribution, and excretion of substances by the body. On the sequence, it seeks to clarify the basic principles of the neurotransmission chemical process, the basis for the functioning of the entire nervous system. Some of the main methods of behavioral pharmacology are explored, with emphasis on those related to substance dependence, such as self-administration procedures, second-order schedules of reinforcement and procedures related to conditioned reinforcement, concurrent schedules choice and behavioral economics. The chapter also discusses a proposal for understanding the relationship between drugs and behavior, including organism modifications related to the effects of psychotropic substances. Finally, some information is briefly presented on three drugs commonly related to the dependence phenomenon, especially in Brazil: alcohol, nicotine, and cocaine.
Keywords: Alcohol; Behavioral pharmacology; Cocaine; Nicotine; Psychopharmacology